On some new fractional integral inequalities - Dahmani, Zoubir; Belarbi, Soumia (J. Inequal. Pure Appl. Math, 2009)
In this paper, using the Riemann-Liouville fractional integral, we establish some new integral inequalities for the Chebyshev functional in the case of two syn- chronous functions.
Keywords: Fractional integral inequalities, Riemann-Liouville fractional integral.